L’évaluation d’impact environnemental et social en péril - Gilles Côté; Jean-Philippe Waaub; Bertrand Mareschal (VertigO)
Implementation of environmental and social impact assessment (ESIA) in public environmental protection schemes and in the performance standards of enterprises is an important development compared to the situation prevailing before the 1970s where only technical and economic considerations were involved in deciding on the implementation of projects. Some consider that the ESIA promotes the integration of environmental and social considerations, from design to project implementation, and consideration of public concerns in decision-making. However, the shortcomings of current practice combined with the pressure to relax ESIA schemes could lead to their marginalization. It is important to provide answers to the many criticisms made by observers and various study committees over the years concerning the relevance of the information contained in the impact studies and the transparency of the analysis process. A solution to this problem lies in the innovation of ESIA methods. The structuring of the approach of evaluation by stakes and the use of multi-criteria decision analysis (MCDA) methods would be all measures likely to improve the situation. The proposals made in this paper are consistent with the characteristics of the collaborative approach to ESIA. They are designed to respond to the issues raised and to meet the challenge posed by a pressing social demand for increased citizen participation in decisions affecting the environment and society.